Nutrition Therapy in Critically Ill Patients Following Cardiac Surgery: Defining and Improving Practice. (September 2017) - Rahman, Adam; Agarwala, Ravi; Martin, Claudio; Nagpal, Dave; Teitelbaum, Michael; Heyland, Daren K.
Background: Malnutrition is a predictor of poor outcome following cardiac surgery. We define nutrition therapy after cardiac surgery to identify opportunities for improvement. Methods: International prospective studies in 2007–2009, 2011, and 2013 were combined. Sites provided institutional and patient characteristics from intensive care unit (ICU) admission to ICU discharge for a maximum of 12 days. Patients had valvular, coronary artery bypass graft (CABG) surgery, or combined procedures and were mechanically ventilated and staying in the ICU for ≥3 days. Results: There were 787 patients from 144 ICUs. In total, 120 patients (15.2%) had valvular surgery, 145 patients (18.4%) had CABG, and 522 patients (66.3%) underwent a combined procedure. Overall, 60.1% of patients received artificial nutrition support. For these patients, 78% received enteral nutrition (EN) alone, 17% received a combination of EN and parenteral nutrition (PN), and 5% received PN alone. The remaining 314 patients (40%) received no nutrition. The mean (SD) time from ICU admission to EN initiation was 2.3 (1.8) days. The adequacy of calories was 32.4% ± 31.9% from EN and PN and 25.5% ± 27.9% for patients receiving only EN. In EN patients, 57% received promotility agents and 20% received small bowel feeding. There was no significant relationship between increased energy or protein provision and 60-day mortality. Conclusion: Postoperative cardiac surgery patients who stay in the ICU for 3 or more days are at high risk for inadequate nutrition therapy. Further studies are required to determine if targeted nutrition therapy may alter clinical outcomes.